Can Islamic Stories be Used as Supplementary English Materials at Islamic Elementary Schools? - Dwi Titi Maesaroh; Aridah Aridah; Desy Rusmawaty (Faculty of Education and Teacher Training of UINSI Samarinda, 2022)
Along with the Islamic schools’ vision and mission, their curriculum generally integrates Islamic values with all subjects taught at schools including the English subject. However, the implementation of the integration is still considered a challenge. This research aimed at confirming the possibility of Islamic stories being used as supplementary materials for English teaching at Islamic elementary schools and give an analysis of how to develop Islamic stories for English teaching materials. This research was carried out at SD IT Insan Karim, Samarinda. Employing a qualitative design, this research used interviews, observation, and documentation to collect data. The interviews with the school principal, English teacher, and one of the parents were carried out to obtain data regarding the curriculum and policies, the target needs, and the learning needs of the English subject. Observation and documentation were managed to support and confirm the findings. Data collected was then analyzed through data condensation, data display, and conclusion drawing/verification. The results show that Islamic stories can be used as supplementary materials to integrate English teaching and Islamic values in the context of Islamic elementary schools. Islamic stories should be developed by considering several aspects and steps such as the curriculum, the language used, illustration and appearance, guidance for teachers, and moral lessons/values. The result of this research could serve as the basis for designing Islamic stories as supplementary materials and have implications for further research and development particularly in the context of Islamic elementary schools.